Comparative analysis of fruit aroma patterns in the domesticated wild strawberries “Profumata di Tortona” (F. moschata) and “Regina delle Valli” (F. vesca) - Negri, Alfredo S.; Allegra, Domenico; Simoni, Laura; Rusconi, Fabio; Tonelli, Chiara; Espen, Luca; Galbiati, Massimo (Frontiers in Plant Science, 2015)
Strawberry is one of the most valued fruit worldwide. Modern cultivated varieties (Fragaria × ananassa) exhibit large fruits, with intense color and prolonged shell life. Yet, these valuable traits were attained at the cost of the intensity and the variety of the aroma of the berry, two characteristics highly appreciated by consumers. Wild species display smaller fruits and reduced yield compared with cultivated varieties but they accumulate broader and augmented blends of volatile compounds. Because of the large diversity and strength of aromas occurring in natural and domesticated populations, plant breeders regard wild strawberries as important donors of novel scented molecules. Here we report a comprehensive metabolic map of the aroma of the wild strawberry Profumata di Tortona (PdT), an ancient clone of F. moschata, considered as one of the most fragrant strawberry types of all. Comparison with the more renowned woodland strawberry Regina delle Valli (RdV), an aromatic cultivar of F. vesca, revealed a significant enrichment in the total level of esters, alcohols and furanones and a reduction in the content of ketones in in the aroma of PdT berries. Among esters, particularly relevant was the enhanced accumulation of methyl anthranilate, responsible for the intensive sweetish impression of wild strawberries. Interestingly, increased ester accumulation in PdT fruits correlated with enhanced expression of the Strawberry Alcohol Acyltransferase (SAAT) gene, a key regulator of flavor biogenesis in ripening berries. We also detected a remarkable 900-fold increase in the level of mesifurane, the furanone conferring the typical caramel notes to most wild species.